Customer satisfaction gap analysis and brand loyalty of prepaid subscribers of Airtel Bangladesh Limited - Saha, Anindya Kumar (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.